Guidance on strategic information: Investor-management disagreement and firm intrinsic value - Agapova, Anna; Volkov, Nikanor (Journal of Banking & Finance, 2019)
We investigate the decision by corporate management to voluntarily disclose information that pertains to a firm's strategy. We find the likelihood of disclosure to be a tradeoff between the benefit of reducing information asymmetry and the cost of investors disagreeing with the strategy; this cost varies with the firm's intrinsic value. Higher levels of investor-management disagreement and of information asymmetry increase the likelihood that managers will disclose strategic information; those at firms with higher intrinsic value, however, are less likely to do so. Our results vary in statistical significance across different proxy specifications, but hold qualitatively. They are robust to the use of exogenous shocks to investor-management disagreement and information asymmetry. The evidence supports a causal link between investor-management disagreement and strategic disclosure.